Analysis of Student Interest in Islamic Financial Products in Yogyakarta - Niswati Hindi Kurnia (Nusantara: Journal of Cultural Research, 2025)
The development of the Islamic financial industry in Indonesia shows great potential, but participation from young people, especially students, still needs to be improved. This study aims to analyze the level of interest of students in Islamic financial products in Yogyakarta and the factors that influence it. The method used is a descriptive quantitative approach with data collection through an online questionnaire. A total of 110 students from various universities became respondents. The results show that students have a relatively high level of knowledge of the basic principles of Islamic finance, such as the prohibition of usury and Islamic contracts. Attitudes towards Islamic products also tend to be positive, especially in terms of convenience and conformity with religious values. Student interest can be seen from the tendency to try and recommend Islamic financial products, although not yet fully realized in real actions. Religious factors, literacy, and digital access have a significant influence in shaping this interest. The implications of these findings emphasize the importance of Islamic literacy education, strengthening digital services, and value-based promotions that are adaptive to the younger generation. This study is expected to be a reference in developing Islamic financial inclusion strategies among students.